2021
DOI: 10.1186/s12864-020-07348-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of the histone acetyltransferase gene family in Triticum aestivum

Abstract: Background Histone acetylation is a ubiquitous and reversible post-translational modification in eukaryotes and prokaryotes that is co-regulated by histone acetyltransferase (HAT) and histone deacetylase (HDAC). HAT activity is important for the modification of chromatin structure in eukaryotic cells, affecting gene transcription and thereby playing a crucial regulatory role in plant development. Comprehensive analyses of HAT genes have been performed in Arabidopsis thaliana, Oryza sativa, barl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 69 publications
3
38
0
Order By: Relevance
“…To predict the exon-intron structure, the gene structure of all candidate A. truncatum WRKY genes was identified by TBtools (used A._truncatum .gff and genes ID), and TBtools software was used for visualization (from GTF/GFF3 File) [ 32 , 33 ]. At the same time, TBtools was used to determine the chromosomal location of the AtruWRKY genes, and their gene ID and sequences were used as the basic data for the searches.…”
Section: Methodsmentioning
confidence: 99%
“…To predict the exon-intron structure, the gene structure of all candidate A. truncatum WRKY genes was identified by TBtools (used A._truncatum .gff and genes ID), and TBtools software was used for visualization (from GTF/GFF3 File) [ 32 , 33 ]. At the same time, TBtools was used to determine the chromosomal location of the AtruWRKY genes, and their gene ID and sequences were used as the basic data for the searches.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the expression of SIP428, an SIR2-type HDAC in tobacco, showed a slight decrease in response to TMV infection [ 29 ]. Recently, it was reported that a list of histone acetyltransferases (HAT) showed elevated expression when the inoculation with RNA virus occur in Triticum aestivum [ 45 ]. Although a previous report had confirmed that histone deacetylase NbHDA6 influenced the infection of TYLCV, a DNA virus, through interaction with methyltransferase 1 (MET1) and TYLCV V2 protein [ 28 ], there is no evidence to prove whether histone acetylation and deacetylation regulate the stress response to DNA virus pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen-induced histone modification is a hotspot of research. Histone acetylation and deacetylation were involved in host defense responses to virus pathogens [ 28 , 29 , 30 , 45 , 50 ]. HD2C is a well-studied and characterized HDAC, whose function is established not only in plant development but in plant abiotic and biotic stress responses [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…27), and wheat (31) (ref. 41). From the phylogenetic analysis, it can be seen that three sister pairs, one triplet, and one quadruplet were identi ed within the SiHAT family.…”
Section: Characterization Of the Expanded Hat Gene Family In Foxtail ...mentioning
confidence: 97%